A Review of Continuous Assessment Learning Activity (CALA) in Zimbabwe: 2017- 2023 - Masiiwa, Spencer Tinashe; Last, Matsiwira (CV. Literasi Indonesia, 2024)
The major goal of this paper was to do a review of the CALA in Zimbabwe. Informed by the major tenets of progressivism as a theory of education, the government of Zimbabwe through the Ministry of Primary and Secondary Education (MoPSE), embarked on a curriculum review exercise in 2015. The study employed secondary data. A closer and thorough inspection of the key stakeholders’ overview of CALA shows that fell short of expectations due to financial, ethical, and moral challenges associated with it. This paper concludes that regardless of the immense benefits of CALA, its adoption and implementation have been met with mixed feelings between and among stakeholders in the education sector and this has overshadowed the significance and relevance of CALA in the context of Zimbabwe. Further, this study concludes that for the period under review (2017- 2023), the Ordinary Level pass rate after the introduction of CALA has been fluctuating from one year to another which is similar to trends observed before the introduction of CALA. The researchers recommend the capacitation and active involvement and participation of teachers through attractive remuneration and training workshops as a panacea in the implementation of any curriculum review since teachers are the key drivers in such a process.